The Responsiveness of Liquid Fuel Price towards COVID-19 and Exchange Rate Fluctuations - Habanabakize , Thomas; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2022)
The petrol price plays an important role in all types of business and economic activities, especially in South Africa. The outbreak of the COVID-19 pandemic and the volatility of the exchange rate are some of the current challenges in the South African economy and these factors might have significant implications on domestic petrol fuel prices. In the last two years, the petrol price has experienced a drastic increase in the South African commodity market. The current study investigated the effect of the COVID-19 pandemic and exchange rate fluctuations on petrol prices in South Africa for the period between March 2020 and June 2022. The autoregressive distributed lag (ARDL) model was employed to establish the long-run and short-run relationship between COVID-19 new infections, exchange rate and petrol price in South Africa. The result revealed that both exchange rate and COVID-19 infections negatively influence the petrol price in the long run. However, in the short-run exchange rate has a positive impact on petrol price while the latter is negatively affected by increases in COVID-19 new cases of infection. To maintain a steady state of petrol prices and reduce the impact of petrol price fluctuations, the study recommends the implementation of monetary policies that strengthen the domestic currency accompanied by social awareness programmes on COVID-19 management.